CSNK2A2 promotes hepatocellular carcinoma progression through activation of NF-κB pathway - Shuang Yang; Li Rong Peng; Ai Qing Yu; Jiang Li (Annals of Hepatology, 2023)
Introduction and Objectives: Breast and non-small cell lung cancers harbor an upregulated CSNK2A2 oncogene that encodes the protein kinase CK2 alpha', a catalytic subunit of the highly conserved serine/threonine kinase CK2. However, its role and biological significance in hepatocellular carcinoma (HCC) remains unclear. Materials and Methods: Western-blotting and immunohistochemistry were used to measure the expression of CSNK2A2 in HCC tumor tissues and cell lines. CCK8, Hoechst staining, transwell, tube formation assay in vitro and nude mice experiments in vivo were used to measure the effects of CSNK2A2 on HCC proliferation, apoptosis, metastasis, angiogenesis and tumor formation. Results: In the study, we showed that CSNK2A2 was highly expressed in HCC comparison with matched control tissues, and was linked with lower survival of patients. Additional experiments indicated that silencing of CSNK2A2 promoted HCC cell apoptosis, while inhibited HCC cells migrating, proliferating, angiogenesis both in vitro and in vivo. These effects were also accompanied by reduced expression of NF-κB target genes, including CCND1, MMP9 and VEGF. Moreover, treatment with PDTC counteracted the promotional effects of CSNK2A2 on HCC cells. Conclusions: Overall, our results suggested that CSNK2A2 could promote HCC progression by activating the NF-κB pathway, and this could serve as a biomarker for future prognostic and therapeutic applications.